2021
DOI: 10.1128/mbio.01067-21
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase-like 3 Modulates Severe Acute Respiratory Syndrome Coronavirus-2 RNA N6-Methyladenosine Modification and Replication

Abstract: Internal chemical modifications of viral RNA play key roles in the regulation of viral replication and gene expression. Although potential internal modifications have been reported in SARS-CoV-2 RNA, the function of the SARS-CoV-2 N6-methyladenosine (m 6 A) modification in the viral life cycle is unclear.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 72 publications
(86 reference statements)
3
57
1
Order By: Relevance
“…At the epigenetic level, arginine alters RNA methylation via methyltransferase like 14 (METTL14) interaction with N6-methyladenosine (m6A), a mechanism documented in COVID-19 pathogenesis ( Li et al., 2021 ; Zhang et al., 2021 ). Interestingly, a dysfunctional m6A methylome was recently reported in tauopathies, implicating RNA methylation in these disorders ( Jiang et al., 2021 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…At the epigenetic level, arginine alters RNA methylation via methyltransferase like 14 (METTL14) interaction with N6-methyladenosine (m6A), a mechanism documented in COVID-19 pathogenesis ( Li et al., 2021 ; Zhang et al., 2021 ). Interestingly, a dysfunctional m6A methylome was recently reported in tauopathies, implicating RNA methylation in these disorders ( Jiang et al., 2021 ).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%
“…These data were validated using the orthogonal meRIP-Seq methodology ( 61 , 110 ) and also served to show that inhibiting the enzymatic activity of METTL3 led to reduced titers of both SARS-CoV-2 and HCoV-OC43. The installation of m 6 A on a small number of SARS-CoV-2 sgRNAs was further validated by additional studies ( 111 , 112 ) using comparative DRS approaches allied with Tombo, MINES, and m6ANet. Another recent study utilized Tombo to show that the SARS-CoV-2 epitranscriptome remained stable during infection of Vero cells ( 113 ).…”
Section: Nanopore-mediated Detection Of Rna Modifications In Viral Co...mentioning
confidence: 95%
“…Expression levels of the eraser FTO are reduced 48 hpi, while ALKBH5 is not affected. All these enzymes are normally present in the nucleus but colocalize in the cytoplasm when the cell is infected [22]. Finally, YTHDF members, such as YTHDF1-3, YTH domain containing (YTHDC) 1, and YTHDC2, do not change during the infection [22].…”
Section: Introductionmentioning
confidence: 99%
“…All these enzymes are normally present in the nucleus but colocalize in the cytoplasm when the cell is infected [22]. Finally, YTHDF members, such as YTHDF1-3, YTH domain containing (YTHDC) 1, and YTHDC2, do not change during the infection [22]. Liu et al demonstrated that an increase of viral replication occurred by knocking down METTL3, METTL14, and YTHDF2, while, on the contrary, when the ALKBH5 was knocked down, SARS-CoV-2 infection drastically decreased [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation